Pappasang To Riolo: Belajar Dari Petuah Leluhur Dalam Membentuk Siswa Berkarakter - Subair, Ahmad (Universitas Negeri Makassar, 2021)
This paper tries to look at the irreverent phenomena that occur in students today, and to find a way out through a series of events in the past with the value of local wisdom in the past. There are two things (more precisely an offer) to be conveyed in this paper in solving this problem. First, an explanation of the value of local wisdom contained in pappasang to riolo, the second tells about the exemplary suri to-riolo (ancestors). These two things are integrated into the historical material and conveyed to students so that students with character can be created. This paper uses a qualitative research method with an anthropological-historical approach in seeing the character (value) of students who experience moral degradation. The results of this study are a new model of character education approach using culture as a role model.